Sartorial Fandom Fashion, Beauty Culture, and Identity - Affuso, Elizabeth; Scott, Suzanne (University of Michigan Press, 2023)
In recent years, geeks have become chic, and the fashion and beauty industries have responded to this trend with a plethora of fashion-forward merchandise aimed at the increasingly lucrative fan demographic. This mainstreaming of fan identity is reflected in the glut of pop culture T-shirts lining the aisles of big box retailers as well as the proliferation of fan-focused lifestyle brands and digital retailers over the past decade. While fashion and beauty have long been integrated into the media industry with tie-in lines, franchise products, and other forms of merchandise, there has been limited study of fans' relationship to these items and industries. Sartorial Fandom shines a spotlight on the fashion and beauty cultures that undergird fandoms, considering the retailers, branded products, and fan-made objects that serve as forms of identity expression. This collection is invested in the subcultural and mainstream expression of style and in the spaces where the two intersect. Fan culture is, in many respects, an optimal space to situate a study of style because fandom itself is often situated between the subcultural and the mainstream. Collectively, the chapters in this anthology explore how various axes of lived identity interact with a growing movement to consider fandom as a lifestyle category, ultimately contending that sartorial practices are central to fan expression but also indicative of the primacy of fandom in contemporary taste cultures.